(untitled) (Research, Society and Development, 2024)
Imuno TF® is a food supplement composed of oligo- and polypeptides with roles in the immune system. It has been previously demonstrated that Imuno TF® positively regulated Th1 cytokines while decreasing Th2 cytokines (reduced secretion of IL-10 and increased secretion of IL-6 and TNF-α). Here we aimed to investigate the actions of Imuno TF® on the frequency of stimulated CD8+ and CD4+ T-cell populations and their cytokine productions. Human lymphocyte cultures were used for that, and IL-2, IFN-γ, IL-4, IL-5, IL-7, IL-13, and IL-35 were quantified by ELISA and RT qPCR. The frequency of CD4+ and CD8+ populations was investigated through flow cytometry. We observed an increased frequency of CD8+ T-cells after the combined stimulation of cells with Imuno TF® and ConA compared to controls. No differences were observed regarding the frequency of CD4+ T-cells. In addition, a significant increase in IL-2, IL-7, and IFN-γ levels was observed, while IL-4, IL-5, and IL-13 presented reduced levels. No alterations were observed in IL-35 levels. Our results suggest that the Imuno TF® can potentially increase the CD8+ T-cell population by positively regulating cytokines associated with Th1 response and increased IL-7 levels while reducing Th2 cytokine-mediated immune responses.